2019
DOI: 10.1016/j.jaci.2019.08.033
|View full text |Cite|
|
Sign up to set email alerts
|

Exacerbation-prone asthma in the context of race and ancestry in Asthma Clinical Research Network trials

Abstract: Exacerbations in 1,840 Asthma Subjects from 12 Clinical Trials (Median Observation Period=126-379 Days) Blacks (N=161) Genetic African Ancestry >82% is a Risk Factor for Exacerbations in Self-Reported Blacks. Whole-Genome Ancestry Estimated in Subgroup Factor for Exacerbations eported Blacks. Whites (N=489) p=0.03 Exacerbation-Prone Asthma in the Context of Race and Ancestry in Asthma Clinical Research Network Trials Background: Minority groups of African descent experience disproportionately greater asthma mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
(119 reference statements)
1
17
0
Order By: Relevance
“…Comorbidities are highly prevalent among EPA patients. We did not find a correlation between EPA and rhinitis or GERD, which were previously reported to be associated with increased exacerbation risk in Blacks [18]. A possible reason is that the prevalence of GERD in East Asia (2.5–7.8%) is much lower than that in North America (18.1–27.8%), South America (23.0%), and Europe (8.8–25.9%) [56].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Comorbidities are highly prevalent among EPA patients. We did not find a correlation between EPA and rhinitis or GERD, which were previously reported to be associated with increased exacerbation risk in Blacks [18]. A possible reason is that the prevalence of GERD in East Asia (2.5–7.8%) is much lower than that in North America (18.1–27.8%), South America (23.0%), and Europe (8.8–25.9%) [56].…”
Section: Discussionmentioning
confidence: 58%
“…A more recently published study based on multiethnic individuals from 12 Asthma Clinical Research Network and Asthma Net trials showed that the risk factors of EPA differed according to race. Grossman et al [18] identified chronic rhinosinusitis, allergic rhinitis, and GERD were only associated with increased exacerbation risk in Blacks rather than Caucasians. Since few studies focus on EPA in Asians and there are no available data from a Chinese population, it is unclear whether these risk factors contribute to frequent exacerbations in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…We performed a two-stage GWAS and identified a novel locus for susceptibility to asthma with exacerbations that reached genomewide significance in the combined meta-analysis. The high asthma prevalence among African-admixed individuals, particularly in developed countries, [6][7][8][9][10] suggests a shared genetic basis that may be a risk factor for asthma under environmental influences that are absent in non-Westernized societies. 8 In this work, we leveraged this specific genetic background to identify a novel locus for severe asthma exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…6 Moreover, African ancestry has been associated with a higher risk of developing asthma among African Americans 7 and Puerto Ricans, 8 as well as with an increased risk of exacerbations among African Americans. 9,10 These data point to a genetic component potentially contributing to the disparities in asthma exacerbations.…”
Section: Introductionmentioning
confidence: 94%
“…First, we explored a highly specific subset of patients with severe asthma. The response to poly I:C may vary across asthma endotypes, particularly in exacerbation-prone subgroups [39][40][41] . Second, we examined PBMCs, while other studies have evaluated the airway compartment 11,12 .…”
Section: Discussionmentioning
confidence: 99%